Alternating current electroluminescence from GaN-based nanorod light-emitting diodes. (August 2021) - Wang, Kun; Chen, Peiqi; Chen, Jingjing; Liu, Ye; Wu, Chaoxing; Sun, Jie; Zhou, Xiongtu; Zhang, Yongai; Guo, Tailiang
Highlights: Nanorod-LEDs are fabricated by using ICP-RIE. AC-driven nanorod-LEDs (AC-nLEDs) are realized. Single-dielectric AC-nLED is demonstrated. Double-dielectric AC-nLED is demonstrated. AC-nLEDs are highly sensitive to driving frequency. Abstract: Alternating current (AC)-driven electroluminescent (EL) devices have attracted widespread attention due to their special advantages. Under the trend of nanoscale miniaturization in optoelectronics, AC-driven EL devices with nanoscale are highly desirable to be applied to nano-optoelectronic integrated circuits. In this work, GaN-based nanorod LEDs (nLED) are used as nanoscale emitters to fabricate AC-driven nano-EL device, namely, AC-nLED. Two configurations including single-dielectric AC-nLED and double-dielectric AC-nLED without carrier injection are demonstrated. The electrical and optical characteristics of single-dielectric AC-nLED and double-dielectric AC-nLED are demonstrated, which have completely different frequency responses. The working mechanisms and origin of the difference in frequency response are discussed. Our work presents an alternative device configuration for obtaining AC-driven nano-EL devices, which are expected to be used in nano-photonic systems and nano-pixel light-emitting displays.